(untitled) - Yendra, Rado
ALLAH have   mentioned of rain  in  the  Qur'ari as much as 55 times, this  of course can  be  concluded that  the  rain  is the  most  important part  created by ALLAH as a mercy to the  universe and  its contents. The Khazanah of rain has been  clearly expressed  in the  Qur'an.  and Hadith.    Khazanah    will    be    clarified   with     rain    parse    some information that  has  been   reported in  the   Word of ALLAH and  the Hadith of  the  Prophet Muhammad from   the  standpoint  of  science. Size  rain  in the  letter reportedly Mu'minuri 18 and  Nur  43 and  also the     differences  of  rain   each   year   reported  in  the   hadith  Wl71 be explained   through   science   (statistics).   Size    rain    appropriately defined  based  on  the   Word of  ALLAH that   can  provide  excellent benefits   to   uncover  the    treasures   of   rain    through   models  of statistical science, especially in generating  estimates  of  the  rainfall measurements for  the foreseeable future.  Through the  ~s       reveals the  importance of  the  nature  and  pattern  of  rainfall each   year  as submitted  by  the  Prophet Muhammad,  have   been   able  to conclude that  science has managed to reveal differences in the  nature of rain every yearALLAHhave   mentionedofrain  in  the  Qur'ariasmuchas55times, this  ofcoursecan  be  concludedthat  the  rain  isthe  most  important part  createdbyALLAHasamercytothe  universeand  itscontents. TheKhazanahofrainhasbeen  clearlyexpressed  inthe  Qur'an.  and Hadith.    Khazanah    will    be    clarified   with     rain    parse    some informationthat  has  been   reportedin  the   WordofALLAHand  the Hadithof  the  ProphetMuhammadfrom   the  standpoint  of  science. Size  rain  inthe  letterreportedlyMu'minuri18and  Nur  43and  also the     differences  of  rain   each   year   reported  in  the   hadith  Wl71be explained   through   science   (statistics).   Size    rain    appropriately defined  based  on  the   Wordof  ALLAHthat   can  provide  excellent benefits   to   uncover  the    treasures   of   rain    through   models  of statisticalscience,especiallyingenerating  estimates  of  the  rainfall measurementsfor  theforeseeablefuture.  Throughthe  ~s       reveals the  importanceof  the  nature  and  pattern  of  r